Detection and molecular characterization of ?-lactamase genes in clinical isolates of Gram-negative bacteria in Southern Ecuador - Arevalo Jaramillo, A. (2016)
This work performed a phenotypic and genotypic characterization of 79 clinical isolates of Enterobacteriaceae and Pseudomonadaceae collected in hospitals of Southern Ecuadorin 2013. Our results showed a high incidence of ?-lactamases and ESBLs with blaTEM and blaCTX-M as the prevalent genes, respectively. By direct sequencing of PCR amplicons, the different ?-lactamases and variants of the genes were also distinguished. Our results revealed a predominance of TEM-1 ?-lactamase and the presence of different CTX-M variants with a prevalence of CTX-M-15. Two infrequent CTX-M variants in South America were also identified. To the best of our knowledge, this is one of the first studies describing the genetic characteristics of ?-lactamases in Ecuador.